Ultra-wideband-aided localization for autonomous robots - Nguyen, Hoang Thien (Nanyang Technological University, 2023)
Achieving accurate, reliable and globally consistent localization is a fundamental challenge for autonomous mobile robots. There have been numerous researches in this topic showing impressive performance in various scenarios and with various sensor combinations. In a multi-robot setting, finding the relative positions between robots is another essential issue that inhibits other high level tasks such as obstacle avoidance, path planning and collaborative tasking. These problems are especially critical for Micro Aerial Vehicles (MAVs) since any collisions with the surrounding objects or neighbor robots can be catastrophic. Furthermore, the size, weight and power constraints are much more restrictive for MAVs as opposed to ground or legged robots. In this regard, Ultra-wideband (UWB) provides many advantages compared to traditional sensors such as camera, radar or LiDAR. However, UWB has its own limitations such as being heavily reliant on line-of-sight (LoS) and being unable to provide any information about the environment. For these reasons, designing new methods that can combine UWB and other sensor modalities is a worthwhile endeavour and also the overarching goal of this thesis.